Workplace Stress, Income And Job Satisfaction As Determinants Of Psychological Well-Being Of Private Secondary School Teachers In Ibadan Metropolis (2021)
This study inquiries into the role of workplace stress, income (salary) of teachers and their level of satisfaction in Teacher psychological well-being. The study adopted descriptive survey design of correlation type. A sample of three hundred teachers were selected for the study using simple random sampling. Data were collected using four scale instruments. Three research questions were raised. Data collected were analyzed at 0.05 level of significance using Pearson’s produce moment correlation and multiple regression. The findings revealed that there was a significant positive relationship between the independent variables and the dependent variable. From the regression analysis, it was discovered that stress, income and job satisfaction jointly predicted psychological well-being. This suggests that the three factors combined accounted for variance in the prediction of psychological well-being. More so, the most potent factors were stress (P = .249; t= 5.165;/k0.05) and job satisfaction (P = .175; t= 3.171;/?<0.05). Based on this, it was revealed that reduced job stress and job satisfaction influence teacher’s psychological well-being. This study therefore concludes that moderate job stress and being happy on the job motivates higher job productivity through enhanced psychological well-being among teachers. It also recommended that teachers should know how to manage stress that arises from workplace as this would not pose threat to their health or impair their well-being which may in tum affect their job efficiency.